Arthropod food webs become increasingly lipid‐limited at higher trophic levels. (23rd May 2013) - Wilder, Shawn M.; Norris, Michael; Lee, Raymond W.; Raubenheimer, David; Simpson, Stephen J.; Jordan, Ferenc
Abstract Understanding why food chains are relatively short in length has been an area of research and debate for decades. We tested if progressive changes in the nutritional content of arthropods with trophic position limit the availability of a key nutrient, lipid, for carnivores. Arthropods at higher trophic levels had progressively less lipid and more protein in their bodies compared with arthropods at lower trophic levels. The nutrients present in arthropod bodies were directly related to the nutrients that predators extracted when feeding on those arthropods. As a consequence, nutrient assimilation shifted from lipid‐biased to protein‐biased as arthropods ascended trophic levels from herbivores to secondary carnivores. Successive changes in the nutritional consequences of predation may ultimately set an upper limit on the number of trophic levels in arthropod communities. Further work is needed to examine the influence of lipid and other nutrients on food web traits in a range of ecosystems.